2019
DOI: 10.1111/lang.12344
|View full text |Cite
|
Sign up to set email alerts
|

How Individual Differences Affect Learning of Translation‐Ambiguous Vocabulary

Abstract: This study examined interactions of word and learner characteristics during foreign vocabulary learning, focusing on translation ambiguity and individual differences in cognitive resources and linguistic background (language proficiency, multilingual experience). Fifty-three native Hebrew speakers and Russian-Hebrew multilinguals learned the phonological form of target Arabic words along with their Hebrew translations and definitions. The mapping could be translation ambiguous, with a single Hebrew word transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 85 publications
3
19
2
1
Order By: Relevance
“…Therefore, it might be the case that when proficiency in the language through which learning takes place is higher, there are more cognitive resources available for processing of the newly acquired information (Segalowitz, 2003; Tzelgov & Kadosh, 2009), especially early in learning. This proficiency/resource‐availability proposal is supported by the general observed association between proficiency in the L1 and learners’ ultimate proficiency in the L2 (e.g., Cummins, 1979), and more directly by a recent study in which proficiency in the language through which learning took place modulated learning (Degani & Goldberg, 2019). In that study, Degani and Goldberg compared native Hebrew speakers to Russian–Hebrew multilinguals in learning Arabic words and did not find a multilingual advantage when learning through Hebrew (the L2 of the multilinguals).…”
Section: Background Literaturementioning
confidence: 79%
See 4 more Smart Citations
“…Therefore, it might be the case that when proficiency in the language through which learning takes place is higher, there are more cognitive resources available for processing of the newly acquired information (Segalowitz, 2003; Tzelgov & Kadosh, 2009), especially early in learning. This proficiency/resource‐availability proposal is supported by the general observed association between proficiency in the L1 and learners’ ultimate proficiency in the L2 (e.g., Cummins, 1979), and more directly by a recent study in which proficiency in the language through which learning took place modulated learning (Degani & Goldberg, 2019). In that study, Degani and Goldberg compared native Hebrew speakers to Russian–Hebrew multilinguals in learning Arabic words and did not find a multilingual advantage when learning through Hebrew (the L2 of the multilinguals).…”
Section: Background Literaturementioning
confidence: 79%
“…Sample size was determined based on previous vocabulary learning studies in which item type and participants’ characteristics were observed (Degani & Goldberg, 2019; 30 participants per group, 12 items per condition). Nonetheless, we acknowledge that the estimated power to detect an interaction (of Cohen's d = 0.3) between LOI and item type with 29 participants per group and 15 items per condition is rather low (power = 0.531, using PANGEA; Westfall, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations